1995
DOI: 10.1002/ppsc.19950120405
|View full text |Cite
|
Sign up to set email alerts
|

Inlet Efficiency Study for the TSI Aerodynamic Particle Sizer

Abstract: The paper reports on the particle sampling efficiency of the inlet system for the Aerodynamic Particle Sizer (TSI, Inc., St. Paul MN). Large particles are depleted from the sampled aerosol by two mechanisms: super-isokinetic sampling at the entrance of the inlet, and inertial impaction on the inner nozzle. A fluorometric technique was used to separately characterize these mechanisms. Numerical studies were also performed. The experimental results show that the inlet's overall efficiency drops from around 90% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Griffiths et al (1986) found that the APS underestimated the aerodynamic diameters of Di-EthylHexyl-Sebacate (DEHS) droplets by 4, 10, and 16% for 5, 7, and 10 µm droplets, respectively. Kinney and Pui (1995) have shown that for liquid particles there are substantial impaction losses in the inner acceleration nozzle for particles larger than about 5 µm. These losses may be smaller for non-sticky solid particles.…”
Section: Aerodynamic Particle Sizermentioning
confidence: 99%
“…Griffiths et al (1986) found that the APS underestimated the aerodynamic diameters of Di-EthylHexyl-Sebacate (DEHS) droplets by 4, 10, and 16% for 5, 7, and 10 µm droplets, respectively. Kinney and Pui (1995) have shown that for liquid particles there are substantial impaction losses in the inner acceleration nozzle for particles larger than about 5 µm. These losses may be smaller for non-sticky solid particles.…”
Section: Aerodynamic Particle Sizermentioning
confidence: 99%
“…The MMAD and GSD calculated from the ACI measurements were compared to those obtained from the APS measurements. For measurement of aerosols larger than about 5 ¹m, a correction may be required to compensate for particle deposition in the APS inlet (Kinney 1990) or for internal wall losses in the ACI (Vaughan 1989). The impact of these losses is relatively small for size distributions (such as those measured in this investigation) that have little particle mass larger than about 5 ¹m.…”
Section: Comparison Of Aps and Cascade Impactor Measurements Of Polydmentioning
confidence: 99%
“…1 for details). Whereas outer inlet aspiration has not been well characterized, Kinney and Pui (1995) found inner inlet aspiration to be affected by super-isokinetic sampling conditions: air velocity is approximately 40 cm/s within the outer inlet and approximately 250 cm/s within the inner inlet (Fig. 1).…”
Section: Introductionmentioning
confidence: 95%
“…Generally, sizing accuracy has not been a problem with the APS, except in the case where large droplets having low viscosity and surface tension may deform during acceleration through the sensing zone (Baron, 1986;Bartley, Martinez, Baron, Secker, & Hirst, 2000;Chen, Cheng, & Yeh, 1990). Counting accuracy, however, has been an issue with this instrument (Armendariz & Leith, 2002;Kinney & Pui, 1995;Peters & Leith, 2003).…”
Section: Introductionmentioning
confidence: 96%